Clinical evaluation of reading performance in refractive lens exchange with a diffractive continuous-range-of-vision intraocular lens - Baur, Isabella; Auffarth, Gerd U.; Łabuz, Grzegorz; Stengele, Annette; Hallak, Mustafa; Khoramnia, Ramin (American journal of ophthalmology, 2023)
Purpose - Evaluation of reading performance with a novel presbyopia correcting intraocular lens (IOL) in refractive lens exchange using an electronic reading desk. - Design - Prospective interventional before-and-after clinical study. - Methods - In total, 56 eyes of 28 patients were included. Bilateral implantation of the TECNIS Synergy IOL (Johnson & Johnson Surgical Vision) during a bilateral delayed sequential refractive lens exchange procedure. Uncorrected and distance corrected reading acuity, reading distance, reading speed, and the smallest print size that could be read effectively at a set (40 cm/80 cm) and subjectively chosen near and intermediate distance were assessed using the Salzburg Reading Desk preoperatively and 6 months after surgery. - Results - Uncorrected near reading acuity increased from 0.61 ± 0.16 logarithm of the minimum angle of resolution (logMAR) preoperatively to 0.05 ± 0.09 logMAR postoperatively at the set near distance (40 cm) and from 0.60 ± 0.11 logMAR to 0.07 ± 0.08 logMAR at the subjectively preferred distance (39.6 ± 5.3 cm and 37.7 ± 4.3 cm). Uncorrected intermediate reading acuity was 0.39 ± 0.19 logMAR preoperatively and 0.08 ± 0.07 logMAR postoperatively at the set intermediate distance (80 cm) and 0.43 ± 0.21 logMAR preoperatively and 0.07 ± 0.08 logMAR postoperatively at the preferred intermediate distance (73.5 ± 9.5 cm and 73.3 ± 5.9 cm). - Conclusions - Uncorrected intermediate and near reading function considerably improved after bilateral implantation of the TECNIS Synergy IOL. Patients preferred a closer near and intermediate distance to the set distances. However, reading function was comparable for the set and subjectively preferred distances.